PROGRAM-TARGETED SUPPORT OF THE CONTINUING PROFESSIONAL DEVELOPMENT OF TEACHERS - Sergeeva, Marina; Buntina, Viktoria; Litvishkov, Vladimir; Poliakova, Iana; Medvedeva, Karina; Gilal, Fama; Oganyan, Elvira (Revista Inclusiones, 2019)
Meeting the needs of the education system in a teacher capable to implement innovative changes in the educational process requires fundamentally new technological support. Mastering of innovative behavior by teachers and description of models, forms, types and ways of disseminating innovative pedagogical practices, in accordance with the federal state initiative “Our New School” in Russia, could be considered as one of the most important resources for modernizing the education system as a whole and, in particular, in the aspect of continuing pedagogical education and professional development.